Influence on driving style and fuel consumption with - Mujanovic, Aid (My University, 2011)
The work done at SAAB Automobile AB in Trollhättan is about to study if it is possible to introduce a new mode with focus on facilitating a more economic way of driving. This mode came to be known as the ECO mode, where ECO stands for Economy, which is supposed to ease and advise the driver during the driving itself, for example by tipping which gear should be chosen with a manual transmission, which is thought to be presented at the assistance display, or with an automatic transmission to increase the drivers means to drive more fuel-efficient. The driver is able to chose whether to follow those advices or not, which basically means that the ECO mode is not governing in any way. The ECO mode itself was initiated due to that CO2 credit was promised, in order if car companies could prove positive real life fuel consumption. Practically this would mean, for example, to cut a couple of grams (CO2-emission) when certifying the emission values. Therefore, there is a need to study this scope of work. In this analysis, there is an interest in what effects the ECO mode would contribute with in a vehicle with automatic transmission. A possible introduction of the mode would probably bring both positive and negative signs within a couple of areas, where vehicle control and comfort belongs to the negatives, while fuel consumption, and therefore CO2 emissions, is expected to improve. To answer these questions, data was collected from the standardized driving patterns US, EU and Saabs own defined cycle, the THN-VBG cycle. The tests were performed with two different calibrations, ECO and STD. A summary of the main results follow: EU-cycle Fuel consumption improved by 5 % with ECO mode. Minimal difference regarding the accelerator regulations between ECO & STD. Wider variation in the accelerator positions with ECO mode. Minimal difference in the ability to follow targeted speed between ECO & STD. US-cycle Fuel consumption improved by 5 % with ECO mode. Minimal difference regarding the accelerator regulations between ECO & STD. Wider variation in the accelerator positions with ECO mode. Minimal difference in the ability to follow targeted speed between ECO & STD. THN-VBG cycle Fuel consumption improved by 1,7 % with the ECO mode. Moderate difference regarding the ability to follow instructions, 7 % more regulation with the STD mode. All cycles including real-life driving show an increased use of higher gears. Accelerations levels – The STD calibration reaches a wider interval of acceleration: ranging from 0 m/s2 – 4 m/s2 whilst the ECO calibrated car rarely passes 2,8 m/s2. This would indicate that the ECO calibration promotes a more restrained driving style as data is captured in real-life traffic.
Keywords: Farkostteknik; Hållbar utveckling; Transport; Vehicle Engineering; Sustainable Development; Transport